A fjord with a land-terminating glacier: Meltwater, bio-optics, particulate matter, nutrients, phytoplankton species, and primary production in west Greenland ... - Lund-Hansen, Lars Chresten; Dahllöf, Ingela; Nielsen, Morten Holtegaard (Zenodo, 2023)
The paper describes the bio-optical conditions, particulate matter, nutrients and primary production in a west Greenland fjord with a land-terminating glacier ...